A Fusion Of Discrete Wavelet Transform-based And Time-domain Feature Extraction For Motor Imagery Classification - Fouziah Md Yassin; Norita Md. Norwawi; Nor Azila Noh; Afishah Alias; Sofina Tamam (Jordanian Journal of Computers and Information Technology, 2024)
Indexed by WOS/ Scopus